Internalization of Spiritual Values in the Kanduhai Sko (Sudaih Nuwa): Traditional Ceremony in Sungai Deras Village - Sindayani, Sakini Putri; Mauliddin, Arif Iman; Patrisia, Icha Nurbahira (Contemporary Society and Politics Journal, 2022)
In the Kerinci community, especially Sungai Deras Village, Kanduhai Sko is a tradition that is considered sacred. Display various kinds and styles of worship during the Kanduhai Sko ceremony. This topic is exciting to raise because traditional ceremonies have different religious aspects. Because no community is involved in organizing this sacred ceremony, starting with children, young people, and parents who live and live in Sungai Deras Village beside this community is essential. The findings in this study dedicate religious values to the Kanduhai Sko ceremony in the Sungai Deras community. The conclusions of this study indicate spiritual values in the Kanduhai Sko ceremony for the Sungai Deras community. " Kanduhai Sko (Sudaih Nuwa)" is a form of designation by the people of Sungai Deras Village for the ceremony, which means Kanduhai Sko (finished rice harvest). One day and the preparation of this ceremony takes three days. The method used in this research is qualitative research with a descriptive analysis approach. As for the results of this study, the researcher can see that the form of the process of carrying out the traditional Kanduhai Sko (Sudaih Nuwa) ceremony includes a series of events, namely: animal slaughter, cooking events, release events, martial arts events, eating together and praying together. As for the spiritual values in the Kanduhai Sko formal event, the researchers found several spiritual values, namely, the importance of honesty, the value of worship, the value of hospitality, and the value of faith.